1999
DOI: 10.1212/wnl.53.7.1473
|View full text |Cite
|
Sign up to set email alerts
|

Increased brain serotonin synthesis in migraine

Abstract: Our findings indicating increased brain serotonin synthesis capacity in migraine patients are consistent with previous reports of systemic alteration of serotonin metabolism in patients without aura. Our results also suggest that the mechanism of action of beta-adrenergic antagonists for migraine prophylaxis may involve regulation of serotonin synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
2
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(76 citation statements)
references
References 33 publications
4
69
2
1
Order By: Relevance
“…Fluctuations in 5-HT homeostasis have been documented in migrainous episodes with similar conclusions. Changes in 5-HT serum levels during patient migraine attacks (Ferrari et al 1989) and disruptions within the synthesis (Chugani et al 1999) and metabolism (Ferrari and Saxena 1993) of 5-HT all substantiate the pathophysiological role of 5-HT in migraine pathogenesis.…”
Section: Introductionmentioning
confidence: 83%
“…Fluctuations in 5-HT homeostasis have been documented in migrainous episodes with similar conclusions. Changes in 5-HT serum levels during patient migraine attacks (Ferrari et al 1989) and disruptions within the synthesis (Chugani et al 1999) and metabolism (Ferrari and Saxena 1993) of 5-HT all substantiate the pathophysiological role of 5-HT in migraine pathogenesis.…”
Section: Introductionmentioning
confidence: 83%
“…An imaging study that used a more SERTselective radioligand [ 123 I]ADAM also demonstrated significantly increased brainstem SERT availability in migraineurs than in healthy subjects [13]. Increased brainstem SERT availability together with low serotonin synthesis rate [14] and increased serotonin turnover [15,16] during headache-free phase reflect low synaptic serotonin concentration. Serotonin is an inhibitory neurotransmitter in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Na migrânea os níveis de serotonina durante as crises estão acentuadamente reduzidos 32 . Apesar disto pacientes portadores de migrânea apresentam aumento em sua capacidade de sintese da serotonina 33 . Algumas das drogas que visam a profilaxia de novas crises fundamenta-se na elevação dos níveis serotoninérgicos circulantes 34 .…”
Section: Discussionunclassified